Focus on Grammar through Processing Instruction - Nassaji, Hossein; Fotos, Sandra S. (Teaching Grammar in Second Language Classrooms, 2011)
In this chapter, we will discuss how grammar can be focused on in L2 classrooms through processing instruction. Processing instruction is a particular approach to teaching grammar that is based on how learners interpret and process input for meaning. This approach rests on the assumption that the role of input is central to language acquisition and that grammar can best be learned when learners attend to it in input-rich environments. Theoretically, the approach draws on a model of input processing developed by VanPatten and his colleagues (Lee & VanPatten, 2003; VanPatten, 1996, 2002a). In this approach, an initial exposure to explicit instruction is combined with a series of input-processing activities that aim to help learners create form-meaning connections as they process grammar for meaning. Due to the explicit grammar component of processing instruction, some researchers have equated it with a focus on forms approach (e.g., R. Sheen, 2007). However, VanPatten (2002a) has argued that since the aim of this approach is “to assist the learner in making form-meaning connections during IP [input processing]; it is more appropriate to view it as a type of focus on form” (p. 764) (see Chapter 1 for the distinction between focus on form and focus on forms).